THE ROLE OF EXECUTIVE COMMUNIST PARTY MEMBERSHIP IN EQUITY INCENTIVES AND FIRM PERFORMANCE: EVIDENCE FROM CHINA - Zhao , Zeyi; Jaidi , Junainah; Anak Nipo, Debbra Toria (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2025)
The equity incentive system is widely recognized as an effective mechanism to mitigate the principal-agent problem in modern corporations. Nevertheless, its implementation may encourage executives to prioritize short-term personal gains over long-term firm interests. This study examines whether equity incentives enhance firm performance, whether executives’ Chinese Communist Party (CPC) membership independently contributes to firm performance, and whether CPC membership amplifies the effectiveness of equity incentives. Based on agency theory, using fixed-effects regression on Chinese listed companies that adopted equity incentive plans during 2017-2022, the results show that equity incentives are positively associated with firm performance, CPC membership is linked to favourable firm performance, and CPC executives significantly strengthen the positive relationship between equity incentives and performance. Overall, these findings highlight the dual role of political affiliation, both as an independent driver of firm performance and as a factor that reinforces the effectiveness of incentive mechanisms, offering theoretical insights and practical implications for corporate governance in emerging markets.